MOLECULAR GENETIC IDENTIFICATION OF BACTERIA ISOLATED FROM GOAT MILK (Experimental biology, 2023)
In recent years there has been a steady trend towards an increase in the number of studies on the study of probiotics, which have a beneficial effect on the body: improve the intestinal microflora; contribute to the reduction of pathogenic bacteria; have the ability to produce substances with antimicrobial activity. In order to obtain probiotics from domestic raw materials, molecular genetic identification of bacterial strains was carried out. The object for the isolation of lactic acid bacteria was natural goat milk from the Almaty region, IE "Bekezhanova". Identification of bacterial strains was carried out on an ABI 3500 xL genetic analyzer (Applied Biosystems) using 16S primers 8F and 806R at the Scientific and Practical Center for Microbiology and Virology (Almaty). Phylogenetic analysis was performed using MEGA 6 software. Nucleotide sequence alignment was performed using the ClustalW algorithm. The results were obtained using the method of determining the direct nucleotide sequence of the 16S rRNA gene fragment, followed by comparison of the nucleotide identity with the sequences deposited in the international GenBank database. According to the results of the studies, the isolated strains of lactic acid bacteria according to the GenBank database were assigned to Lactobacillus fermentum (identity above 99.73%). These strains of microorganisms isolated from goat's milk may be promising for the production of domestic food products. On their basis it is proposed to create fermented milk products for preventive purposes.